THE ANALYSIS OF WE THE FEST’S DIGITAL MARKETING COMMUNICATION BY ISMAYA ON INSTAGRAM - Najmussahar, Linda Shafura; Yuliana, Gati Dwi (Istek Widuri Jakarta, 2022)
The shift in the practice of conventional to digital marketing has been utilized by marketers to communicate interactively. We The Fest, a music festival, intensively doing marketing in social media, especially Instagram. This study aims to describe digital marketing communication that Ismaya does through Instagram for We The Fest predicated on their marketing objectives in terms of approach, way of marketing, type of messages and features. The concept used to analyze this research data is marketing communication in social media, MAIN model, medium characteristics and Instagram. This research utilizes a constructivist paradigm with a qualitative approach and type of descriptive research. The instrument used is a researcher and availed by interview guidance. Data amassing technique was done by in-depth interview and observation. The data analysis technique used is Huberman and Miles model and the data validity technique used is source validation. The result of this research shows that We The Fest using audio, visual and sensory approach to their message. It is equipped with the form and type of multimedia messages that contain popular elements, slice-of-life and trigger the user-generated content. When doing accommodation, Ismaya prioritizes the quandary solving that experienced by their audience and responding to them. They also use the response from their audiences to develop communication strategies. We The Fest binds and link with their audiences through loyalty programs and competitions. Not only on Instagram, We The Fest withal publishes their marketing message to other social media, conventional media, and restaurants owned by Ismaya. We The Fest uses varied features of Instagram by taking notice of interactivity, usability and message durability. For further research, hopefully can brought up the comparison between several social media used as marketing communication tools to discover the uniqueness of each platform and ensure which is the most suitable social media that can be used to market music festivals.